An evidence-based approach to the urgent referral of suspected oral cancer in England - Langton, SG (2020)
Background Reports that UK outcomes for several cancers, including oral, were inferior to comparable European countries prompted the UK Government’s ‘NHS Cancer Plan’; a central aim was reduction of late presentation. One key policy was the English ‘two-week rule’ (TWR) system for suspected cancer, specifying a maximum of 14 days between referral and specialist consultation. For oral cancer, little research has been undertaken on several key areas including its influence on stage on presentation and how the system might be improved.